Systematic review of interventions targeting fundamental care to reduce hospital‐associated decline in older patients. (9th July 2021) - de Foubert, Marguerite; Cummins, Helen; McCullagh, Ruth; Brueton, Valerie; Naughton, Corina
Abstract: Aims: To examine the effectiveness of targeted nursing interventions on mobilization, nutrition and cognitive engagement to reduce functional and hospital‐associated decline (HAD) in older patients. Design: Systematic review of experimental studies using randomized and quasi‐experimental designs. Data sources: We searched electronic databases CINAHL, MEDLINE, EMBASE, Cochrane library, google scholar and BMJ quality reports from January 2009 to February 2020. Review methods: We reviewed intervention studies that targeted ward nursing teams to increase mobilization, nutrition or cognitive engagement of older adults. Inclusion criteria included older patients, acute care (medical, surgical and older adult wards) and reporting patient level outcomes. Quality appraisal included the Joanna Briggs Critical Appraisal Checklist for Quasi‐Experimental Studies. Results: From 1729 papers, 18 studies using quasi‐experimental and pre‐post designs were selected. Study heterogeneity necessitated a narrative synthesis. The quality of evidence was low to moderate. All studies used multicomponent strategies, and 10 studies used evidence translation frameworks to align interventions to local barriers. Overall, 74% ( n = 14) of studies reported a significant improvement in the stated primary outcome. Eight studies reported a significant increase in mobilization (e.g., sitting in a chair or walking), and four reported improved functional outcomes. Five studies improved nutrition outcomes (e.g., protein or energy intake), and three studies reported a significant reduction in delirium. Conclusion: Acknowledging methodological limitations, the evidence indicates that nursing teams using evidence‐translation frameworks can improve mobilization, nutrition and cognitive engagement in acute care settings. Future research requires higher‐quality pragmatic trial designs, standardized outcomes, staff co‐designed interventions, evidence‐translation frameworks and patient engagement to make more confident inference about effectiveness. Impact: Nursing teams with the support of hospital management have to address ward and system barriers to prioritize fundamental care to improve patient outcomes. There is sufficient evidence on multicomponent interventions and implementation strategies to inform nurse‐led quality improvement.